Diet, nutrients, and bone health - Anderson, John J. B. 1934-; Garner, Sanford C.; Klemmer, Philip J. (Taylor & Francis, 2012)
"Presenting recent advancements in research findings and the resulting new schools of thought on the physiology of human bone, this comprehensive reference examines information on dietary pattern and specific nutrients in bone health. Written by experts in the areas of nutrition, bone function, and medicine, chapters include research on a variety of bone-related topics including effects of vitamins, nutrients, and antioxidants; dietary requirements; physical exercise; bone hormones; lifestyle and effects through the life cycle; race and ethnicity; and prevention of bone diseases including osteopenia and osteoporosis"--